PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII1 SMP NEGERI 13 PEKANBARU - Nasution, Shelly Prisay; Heleni, Susda; Armis, Armis (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research aims to improve learning process and the student’s mathematics learning outcomes through implementation of Problem Based Learning (PBL) Model. This type of research is Classroom Action Research with two cycle. The research was conducted in class VIII1 SMP Negeri 13 Pekanbaru in the odd semester of the academic year 2018/2019. The subject of this research consist of 40 students. The research instrument consists of learning materials used include Syllabus, Lesson Plan and Student Activity Sheets and instruments for collecting data are observation sheets and test of mathematics learning outcomes. Data analysis techniques in this study are descriptive narrative analysis and descriptive statistics analysis. From the analysis of observation sheets, it can be seen that there is improvement of learning process. The percentage and frequency of students who achieved minimum completeness criteria is increased from the basic score with percentage 45% (18 students) to cycle I with percentage 72,5% (29 students) and 87,5% (35 students) in cycle II. This research concludes that the implementation of PBL model improved the learning process and the student’s mathematics learning outcomes at class VIII1 SMP Negeri 13 Pekanbaru in the odd semester of the academic year 2018/2019.Key Words: Problem Based Learning model, Mathematics Learning Outcomes